Exploring the Role of Decentralization in Resource Marginalization in Kenya - Ajwang, Nicholas Walter Otieno (European Scientific Journal, ESJ, 2023)
Against a background of decentralization in Kenya, limited previous research examines its role in resource marginalization in the country. Specific objectives include identifying the socio-economic sources of resource marginalization and identifying solutions to the socio-economic resource marginalization. The results of the study will improve our understanding of decentralization. Qualitative data was collected and analysed using thematic analysis. Quantitative data was collected and analysed using Statistical Package for the Social Sciences (SPSS). The study found that though decentralization has been used as a vehicle to alleviate poverty, it has led to some form of marginalization of certain key groups in the society. Recommendations for policy and further studies are made from the conclusions emanating from the academic study.